Capital and the Scientific Endeavour. An Appraisal of Some Marxist Contributions to the Debate on the Commodification of Science. Issue 4 (1st October 2020) - Arboledas-Lérida, Luis
Abstract : This article pretends to garner and critically engage with some classic and contemporary contributions made from Marxism about science and its capitalist character. Based on an in-depth literature review, the ultimate goal is to reconstruct those general determinations the academic endeavour is under as seized by capital, regarding the three basic moments of its unity, namely: the content of science (i.e. what science is for), the method of inquiry (i.e. how science intellectually appropriates reality), and the historical form shaping the production of scientific statements (i.e. the evolving relationships of production within science). This paper is divided in two parts: Part I focuses on Marx's own account about science as an alien potency of production, and move afterwards to assessing some contributions on the content of the scientific endeavour as an inner moment of the production of (relative) surplus value. Part II discusses different conceptions held by Marxian scholars on the capitalistically-grounded nature of the method of science, and comments on contemporary analyses on why and how the academe has turned into a(nother) sphere of capitalist accumulation.